Analysis of a delayed and diffusive oncolytic M1 virotherapy model with immune response. (October 2020) - Elaiw, A.M.; Al Agha, A.D.
Abstract: Oncolytic virotherapy (OVT) is a promising therapeutic approach that uses replication-competent viruses to target and kill tumor cells. Alphavirus M1 is a selective oncolytic virus which showed high efficacy against tumor cells. Wang et al. (2016) studied an ordinary differential equation (ODE) model to verify the potent efficacy of M1 virus. Our purpose is to extend their model to include the effect of time delays and anti-tumor immune response. Also, we assume that all elements of the extended model undergo diffusion in a bounded domain. We study the existence, non-negativity and boundedness of solutions in order to verify the well-posedness of the model. We calculate all possible equilibrium points and determine the threshold conditions required for their existence and stability. These points reflect three different fates for OVT: partial success, complete success, or complete failure. We prove the global asymptotic stability of all equilibrium points by constructing suitable Lyapunov functionals, and verify the corresponding instability conditions. We conduct some numerical simulations to confirm the analytical results and show the crucial role of time delays and immune response in the success of OVT.